A focus on adolescent mental health and well-being in Europe, central Asia and Canada - Cosma, Alina (World Health Organisation, 2023)
The Health Behaviour in School-aged Children (HBSC) study is a large school-based survey carried out every four years in collaboration with the WHO Regional Office for Europe. HBSC data are used at national/regional and international levels to gain new insights into adolescent health and well-being, understand the social determinants of health and inform policy and practice to improve young people’s lives. The 2021/2022 HBSC survey data are accompanied by a series of volumes that summarize the key findings around specific health topics. This report, Volume 1 in the series, focuses on adolescent mental health and well-being, using the unique HBSC evidence on the mental health of adolescents aged 11, 13 and 15 years across 44 countries and regions in Europe, central Asia and Canada. It describes the status of adolescent mental health and well-being across a range of indicators, the role of gender, age and social inequality, and how adolescent mental health and well-being has changed over time. Findings from the 2021/2022 HBSC survey provide an important evidence benchmark for current research, intervention and policy-planning.
Keywords: Ageing; Manuscript, Book and Print Cultures; Adolescents; Applied Psychology; CHILD DEVELOPMENT; Child and Adolescent Mental Health; Children/Youth; Educational Psychology; PSYCHOLOGY; PUBLIC HEALTH; Emotional-behavioural Problems; Mental Health/Psychosocial disability; Culture; Gender; Globalization; Poverty; Youth